PEMBELAJAN PAI BERBASIS PROYEK DALAM MENANAMKAN SIKAP SOSIAL SISWA DI SD NEGERI 064979 SETIA BUDI MEDAN - Rosnaida Harahap; Khairuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Instilling social attitudes from an early age is crucial in shaping students' character, especially at the elementary school level. Islamic Religious Education (PAI), as a core subject, plays a strategic role in instilling social values such as empathy, mutual cooperation, tolerance, and responsibility. This study aims to describe how the implementation of project-based PAI learning (PBL) can foster social attitudes in elementary school students. The approach used was descriptive qualitative, with data collection techniques through observation, interviews, and documentation of students and teachers at a public elementary school. The results showed that project-based activities such as creating posters of Islamic values, social actions in the school environment, and group discussions about the stories of the prophets, were able to improve social interaction, teamwork, and a sense of caring among students. Supporting factors for the success of this learning included the role of the teacher as an active facilitator and student involvement in the process. Meanwhile, obstacles faced included limited time and variations in student character. Thus, project-based PAI learning has proven effective in instilling social attitudes in elementary school students and is worthy of being developed more widely at various levels of elementary education.